A descriptive Analysis of Anglicisms used in Ecuadorian Magazines. - Figueroa Herrera, Fabian Roberto (2011)
This is an investigation with a qualitative and quantitativeapproach, carried out in Quito, Ecuador, from April 2010 to March2011, to determine the linguistic phenomenon of anglicisms used inEcuadorian magazines. For this purpose, ten different magazinesedited and published in Ecuador between 2009 and 2010 were usedin order to collect the data collection, three different variables whichincluded cultural, scholarly, and general interest magazines, the onesthat better represented all types of the Ecuadorian population werechosen. The data was analyzed in-depth linguistically andcomparatively, to determine the semantics, syntax, pragmatics, andmorphological aspects of the English words incorporated into thelexicon of the Spanish language.The final aim was to determine the frequency of anglicisms,which variable contained the highest number, and which terms weremostly used, to conclude if the use of anglicisms in Ecuadorianmagazines is a positive or negative addition to the language, and ifthe langzuage is being enriched or deteriorated by them.This research demonstrates that the phenomenon of anglicismsused in Ecuadorian magazines is a reality, and the frequency is highbut not as high as in the oral communication. The higher frequencyin the oral lexicon must be due to the fact that people are morecareful when writing than when speaking. From the 30 most frequent2anglicisms extracted, 67% belonged to general interest magazines,19% to scholarly magazines, and only 14% to cultural magazines.This is due to the fact that in these types of publications the writerstry to use a more formal language. Also, anglicisms are used todescribe technical terms or devices, or they are words related tobusiness, entertainment, and fashion.As conclusions it was found that the English Language and itsculture has a strong influence on the Spanish Language, and that thenumber of anglicisms used depends on the age and area of interest.Also, the anglicisms with the highest frequency of use wereblog/geros and inwLternet, with 34 repetitions, followed closely by fútbolwith 33 repetitions.